Struktur Komunitas Perifiton Pada Lamun Jenis Thalassia hemprichii dan Cymodocea rotundatta di Kawasan Pantai Sanur - Pratama, Putu Satya; Wiyanto, Dwi Budi; Faiqoh, Elok (Journal of Marine and Aquatic Sciences; Vol 3 No 1 (2017)DO - 10.24843/jmas.2017.v3.i01.123-133, 2017)
Seagrass has function as nursery ground, spawning ground, feeding ground and habitat for many coastal organism (benthic, fish and epiphytes). Tourism activities in Sanur beach, the habitat of seagrass, could change the water condition, it indirectly influencing the existences of seagrass plants and periphyton in Sanur beach. The aim of this study are to analyze community structure of periphyton on seagrass leaves ( Thalassia hemprichii and Cymodocea rotundatta ) and its relationship with water parameters in four stations at Sanur beach area that has the unique characteristics. Water parameters measured were temperature, salinity, DO (Dissolved oxyen), pH, nitrate, phosphate, and TSS (Total Suspended Solid). Data analysis using PCA (Principal Component Analysis) to see the parameters that most influence on the abundance of periphyton. The results showed diversity index (H’) of periphyton is moderate, eveness index (E) moderate to high, and dominance index (C) is low to medium. It concluded that conditions of Sanur waters is stable but it is easily changed due to anthropogenic influences. PCA analysis showed that the parameters of the water have different effects on the abundance of periphyton at each seagrass leaves. Periphyton on Thalassia hemprichii was influenced by TSS, while Cymodocea rotundatta was influenced by phosphate, nitrate, temperature, DO, and TSS.
Keywords: seagrass, periphyton, community structure, Sanur beach